Food Away From Home and Self-Perceived Gastrointestinal Health - Chen, Jyh-Jou; Tsai, Li-Yun; Tsai, Jung-Mei; Hsu, Chen-Yuan (Frontiers in Nutrition, 2021)
Dietary behavior is a critical lifestyle factor affecting health. This study aimed to investigate food away from home (FAFH) and its effect on the gastrointestinal (GI) health. A questionnaire-based survey was conducted with 300 participants at a hospital in Liouying, Taiwan. The survey collected demographic information and data on FAFH and GI health. The association of GI health with FAFH consumption behavior was significant (t test, p< 0.05). Body weight status was associated with age (F=5.01, p= 0.01), dietary situation (F=1.96, p= 0.04), number of meals (F=1.85, p= 0.03), dietary preferences (F=2.84, p= 0.00), reasons for FAFH (F=1.86, p= 0.02), FAFH types (F=2.01, p= 0.00), and outcomes associated with FAFH (F=2.51, p= 0.00). GI condition was associated with the number of meals (F=2.55, p= 0.00), level of activity after meals (F=2.16, p= 0.02) and FAFH type (F=1.48, p= 0.04). The results indicated that participants aged 20-40 years had more problems related to their self-perceived body weight status than those aged 41-50years. The results of this study clarify FAFH among people in Taiwan and the effects on GI health and may serve as a reference for relevant behavioral research in food and health studies.